Examining Individual and Environmental Factors Associated with Emergency Preparedness Among People with Disabilities in China - Yue Xu; Bo Chen; Kelly Hsieh (Disabilities)
Background: People with disabilities, particularly those from developing countries, often fare worse during disasters, pandemics, and other emergencies. China is located in the most disaster-prone region in the world. However, no study has examined emergency evacuation planning among people with disabilities in China. The latest literature on emergency preparedness tends to focus on individual-level factors such as demographic characteristics, self-efficacy, and disability status. A focus on individual-level factors overlooks the importance of environmental influences on disaster preparation. Objective: This paper explores how individual and environmental factors are associated with emergency preparedness among people with disabilities in China. Methods: Two hundred and forty-eight people with various disabilities filled out an online cross-sectional survey on the level of emergency preparedness among people with disabilities in China. We conducted a hierarchical logistic regression to examine which environmental-level factors are associated with emergency preparedness after controlling for individual-level factors. Results: The results show that when entering only individual-level factors, self-efficacy in evacuation and previous emergency experiences are significant factors associated with being prepared. After including the environmental-level factors, self-efficacy remains significant. People with a physical disability and those from Hubei province, when compared with respondents from the rest of China, are less likely to be prepared. Another protective factor other than self-efficacy is being part of an online disability peer-support group. Conclusions: When designing risk management interventions, public health officials should consider both individual- and environmental-level factors. Using an online peer-support community may be considered an innovative component when designing these interventions.